2017
DOI: 10.1111/iwj.12867
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors associated with infection in patients with chronic leg ulcers

Abstract: Leg ulcers are hard to heal. Infection causes delayed healing, negatively impacting patients' quality of life, the healthcare system, and society. Early recognition of patients at high risk of infection is essential to prevent complications and reduce negative impacts. However, at present, factors associated with infection in this population are not yet clearly understood. The study aimed to identify factors that were significantly associated with infection in chronic leg ulcers. A sample of 561 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 33 publications
9
18
0
Order By: Relevance
“…Depression was significantly associated with infection with the risk of infection increasing five times in those who were diagnosed with depression in a previous study of 561 patients with chronic leg ulcers (Bui, Edwards, et al, 2018a), and patients with CLUs who were also diagnosed with depression were three times more likely to have infection compared to those without depression in another study of 636 patients with chronic leg ulcers (Bui, Finlayson, et al, 2018b). In the current study, we found 15.6% of patients reported being diagnosed with depression.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Depression was significantly associated with infection with the risk of infection increasing five times in those who were diagnosed with depression in a previous study of 561 patients with chronic leg ulcers (Bui, Edwards, et al, 2018a), and patients with CLUs who were also diagnosed with depression were three times more likely to have infection compared to those without depression in another study of 636 patients with chronic leg ulcers (Bui, Finlayson, et al, 2018b). In the current study, we found 15.6% of patients reported being diagnosed with depression.…”
Section: Discussionmentioning
confidence: 89%
“…While there could be a bidirectional relationship between depression and infection as patients with infection had a higher rate of depressive symptoms (Cancienne, Mahon, Dempsey, Miller, & Werner, ), depression has been identified as a risk factor for infection in general skin infections (Andersson et al, ) and in acute wounds (Cancienne et al, ; Olsen et al, ). Depression was significantly associated with infection with the risk of infection increasing five times in those who were diagnosed with depression in a previous study of 561 patients with chronic leg ulcers (Bui, Edwards, et al, ), and patients with CLUs who were also diagnosed with depression were three times more likely to have infection compared to those without depression in another study of 636 patients with chronic leg ulcers (Bui, Finlayson, et al, ). In the current study, we found 15.6% of patients reported being diagnosed with depression.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The natural history of VLU disease is a cycle of prolonged healing and recurrence . Factors that commonly contribute to poor healing include local causes, such as wound infection, tissue hypoxia, trauma, necrotic tissue as well as systemic diseases such as diabetes …”
Section: Introductionmentioning
confidence: 99%